Responses to global change: a study of bee body size across a century of environmental variation - Levendofsky, Piper, author; Mola, John, advisor; Zwick-Tapley, Sarah, committee member (Colorado State University. Libraries, 2026)
Bees are vital pollinators, they provide invaluable ecosystem services to humans and play a crucial role in the success of agricultural production and overall ecosystem function. There are over 1,000 species of native bees present within Colorado, many of which are experiencing population declines and morphological changes due to unpredictable climate and ecosystem conditions associated with climate change. This threat to native bees has sparked an increase in research that aims to provide information about species trends over time to better inform conservation efforts. In this study, an intraspecific analysis of three bee species (Agapostemon texanus, Bombus pensylvanicus, Anthophora montana) was completed with museum specimens to explore the changes in bee body size over time and how varying climate conditions impact their development. Museum specimens were used to measure intertegular distance (ITD), the distance between tegulae across the thorax as a proxy of bee body size (Cane 1987). Over 180 individuals were measured for each species, all from various dates and locations throughout Colorado and Southern Wyoming, spanning 124 years. After all specimens were measured, a comprehensive analysis was completed to examine bee body size shifts over the course of the collected specimens and correlations with climate. The results indicate a significant decline in body size for B. pensylvanicus and A. texanus, and a significant increase in body size for A. montana over time. B. pensylvanicus also showed a significant decrease in size when elevation increases. Further analysis revealed a significant relationship between female A. texanus and growing season precipitation. No significant correlation was found between temperature and body size for any species. The results from this study represent a combination of factors resulting in physical adaptations. Ultimately, this study highlights how environmental changes may be subtly shifting bee morphological characteristics causing adaptations within and across species, which could lead to cascading effects within ecosystems.
Keywords: pollinators; climate change; native bees; morphological changes